Not Yet a Duck - Tim Daugherty; Dana Paliliunas; David Zimmerman; Natalie Curry; Tanya Whipple; Leslie Echols; Paul Deal; Saylor Strength (Journal of College Orientation, Transition, and Retention)
Online baccalaureate programs now serve a quarter of American degree-seeking students.  As those programs proliferated in the past decade, host institutions tended to “unbundle” academic affairs and student affairs (often neglecting the latter in the design and delivery of online programs).  And so, while online programs opened the door for students facing barriers, the programs might not be conveying the full set of social, personal, and professional benefits of a college education.  Herein, we describe our initiation of a data-driven effort to enrich online degree programs.